PCSK9과 LDL-C: 운동의 역할 - 진재호; 조우연; 노지헌; 이상기 (Exercise science (Seoul, Korea), 2020)
PURPOSE: Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9) is a pivotal regulator of low lipoprotein-cholesterol (LDL-C) and LDL receptor (LDLR) metabolism, and the interest in PCSK9 has increased in cardiovascular diseases. Exercise reduces blood LDL-C via PCSK9-LDLR pathway in the liver and the vasculature. However, the mechanism of exercise-induced inhibition of PCSK is unclear. The aim of this review is to describe the role of exercise on PCSK9-LDLR axis in cardiovascular diseases. METHODS: This study review 34 previous studies focusing on the effect of exercise on PCSK9 in the human and animal. RESULTS: The effects of exercise and lifestyle intervention on hepatic and circulating PCSK9 are controversial. However, exercise consistently increases hepatic LDLR, and inhibits atherosclerosis via suppression of PCSK9 and LOX-1 in atherosclerotic region. CONCLUSIONS: Even though experimental data are still very limited, exercise training can improves blood LDL-C via inhibition of PCSK9 and enhancement of LDLR in liver and vasculature. The study of exercise on PCSK9 are urgently needed. KCI Citation Count: 0